PENGARUH KONSENTRASI DAN SELANG WAKTU PEMBERIAN EFFECTIVE MICROORGANISMS 4 (EM-4) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAPAS (Gossypium hirsutum L.) - Arsyid, Moh. Amri; Chozin, M. A.; Zaman, Sofyan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1998)
The objective of this experiment is to study the effect of concentration and application interval of EM4 on growth and yield of cotton. The experiment was held in KP Sindangbarang Bogor from March to August 1996, using RCD with two factors and three replications. The first factor was EM4 concentration which were 0 ml L-1 water, 5 ml L-1 water, 10 ml L-1 water, 15 ml L-1 water, and 20 ml L-1 water. The second factor was application interval which were 5, 10, and 15 days. The result shows that the concentration of 5 ml L-1 water significantly affected the vegetative growth. But in the contrary, application interval and its interaction do not give the similar effect. The generative growth were significantly affected by concentration and application interval and its interaction. The best combination for maximum cotton yield is in concentration of 5 ml L-1 water and application interval 10 days, and for maximum seeded cotton yield is 5 ml L-1 water and 15 days.